Coupling Photothermal Effect into Efficient Photocatalytic H2 Production by Using a Plate‐like Cu@Ni Core‐shell Cocatalyst. Issue 10 (29th April 2020) - Guo, Xinyang; Xue, Fei; Xu, Shikai; Shen, Shaohua; Huang, Hongwen; Liu, Maochang
Abstract: The general moderate reaction condition in solar photocatalytic hydrogen production (i. e., near ambient pressure, room temperature) makes interfacial mass and energy transfer extremely slow, even by employing a cocatalytic material (usually in the form of noble metal nanoparticles or their counterparts). Herein, by fabricating well‐defined Cu@Ni core‐shell nanoplate cocatalyst and further incorporating it with a g‐C3 N4 photocatalyst, we demonstrate that interfacial processes could be significantly improved by coupling localized photothermal effect into a cocatalyst. Specifically, Cu nanoplate can induce localized strong hot spots on Ni nanoparticles via a visible‐light‐driven surface plasma resonance effect. As a result, photogenerated electrons transferred from g‐C3 N4 to Ni, could be elevated to a more energetic state, leading to a substantially improved photocatalytic activity toward H2 evolution from water. The highest hydrogen generation rate reaches 55 μmol h −1 g −1, 110 times of that pristine g‐C3 N4 . This work indicates that photoelectric and photothermal effects can be effectively coupled by integrating metal hetero‐nanoparticles. Abstract : How do you wave ? In this work, we realized the coupling of localized photothermal effect into a cocatalytic material by developing a unique core‐shell Cu@Ni nanoplate cocatalyst for efficient photocatalytic H2 production from water. Specifically, Cu nanoplate could induce localized hot spots on Ni nanoparticles via a visible‐light‐driven surface plasma resonance effect. As a result, photogenerated electrons transferred from g‐C3 N4 to Ni, could be elevated to a more energetic state, leading to a substantially improved photocatalytic activity.